Exploring the relationship between communication and success of construction projects - Malik, Summaira (2022)
Funding Information: Funding: This research was supported by Instituto Politécnico de Lisboa. Publisher Copyright: © 2021 by the authors. Licensee MDPI, Basel, Switzerland.